Insecurity in Nigeria, it Multipler Effects on African Peace And Economy: an Analysis of Complex- Interdependece Theory - Alfakoro, Abubakar S Yushau; Ogirima, Ibrahim Salawu (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
Nigerian as a nation has been experiencing a very low or, to say, a relative level of peace for over a decade now. The resulted effects of its insecurity have not only internal implications but also constituted external effects as it has tampered with its external relationships (foreign policies). This reality over time has led to the adoption of stringent policies which are not in line with its foreign policies and has also earned the country bad image in the international system. Nigeria, being the giant of Africa, one of the populous world nations, and also endowed with other numerous natural resources, has, over the years, been suffering from security challenges ranging from book-harams, militants, bandits, and kidnappings, etc. These challenges, mandated the closures of land borders, reduction in the refining of crude oils, discouragement of investors, immoral name in the international system, and surplus budget on military hardwares, etc. The rationale behind this study is to assess the effects of insecurity on African peace and economy with peculiarities to countries sharing borders with Nigeria. The paper made use of secondary sources of materials through a comprehensive review of literature on the subject matters under investigation. This article recommends that necessary steps and solutions needs to be employed to curb insecurity before it becomes cancerous or escalates beyond control.